PENGARUH JENIS DAN KOMPOSISI PUPUK KANDANG AYAM DAN PUPUK NPK TERHADAP SERAPAN NITROGEN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) VARIETAS LEMBAH PALU DI ENTISOL SIDERA - Prastya, David; Wahyudi, Imam; Baharudin, Baharudin (AGROTEKBIS, 2016)
This study aims to determine the effect of the type and composition as well as the interaction of inorganic fertilizers (NPK) and organic fertilizers (piles of chicken) to the N uptake in entisols Sidera. This study uses a randomized block design (RBD), which consisted of 9 treatments were repeated 3 times so that there 27 experimental units. The treatment consisted of control and 2 types of fertilizers inorganic fertilizers doses of 150 kg/ha, inorganic fertilizer dose of 300 kg/ha of organic fertilizer dose 10 ton/ha and a dose of organic fertilizer 40 ton/ha. Data were analyzed using analysis of variance to determine the effect between treatments. If the results of analysis of variance showed a significant effect, then tested further by using 5% honest significant difference (HSD 5%). The results showed that administration of inorganic fertilizer (NPK) dose of 300 kg/ha significantly increased uptake of nitrogen to crops, organic fertilizer (piles of chicken) dose 40 ton/ha very significantly increased uptake of nitrogen and no significant interaction between the treatment of inorganic fertilizers (NPK) and organic puopuk (piles of chicken) on plant nitrogen uptake of onion (Allium ascalonicum L.).Â Key Words: Entisol Sidera, Onion, nitrogen uptake.